2019 9th International Conference on Computer and Knowledge Engineering (ICCKE) 2019
DOI: 10.1109/iccke48569.2019.8964956
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Guided Version of 2D UNet for Automatic Brain Tumor Segmentation

Abstract: Gliomas are the most common and aggressive among brain tumors, which cause a short life expectancy in their highest grade. Therefore, treatment assessment is a key stage to enhance the quality of the patients' lives. Recently, deep convolutional neural networks (DCNNs) have achieved a remarkable performance in brain tumor segmentation, but this task is still difficult owing to high varying intensity and appearance of gliomas. Most of the existing methods, especially UNet-based networks, integrate low-level and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Recently, the attention mechanism has been well applied in the field of image segmentation [ 19 , 20 , 21 ]. Squeeze and Excitation Block has also been verified to be applicable to medical image segmentation [ 26 ]. Similarly, in our proposed ACAU, in order to improve the quality of the representation generated by the network, we use Squeeze and Excitation Block [ 16 ] in each upsampling block, adaptively weight the channel, use global information, and selectively emphasize Information features, suppress useless features.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the attention mechanism has been well applied in the field of image segmentation [ 19 , 20 , 21 ]. Squeeze and Excitation Block has also been verified to be applicable to medical image segmentation [ 26 ]. Similarly, in our proposed ACAU, in order to improve the quality of the representation generated by the network, we use Squeeze and Excitation Block [ 16 ] in each upsampling block, adaptively weight the channel, use global information, and selectively emphasize Information features, suppress useless features.…”
Section: Methodsmentioning
confidence: 99%
“…Table V and Fig.8demonstrate the comparison results. With reasonably fewer parameters than Noori et al[49] and Shi et al…”
mentioning
confidence: 89%
“…Several researches [ 8 , 9 , 10 , 11 ] have demonstrated that 3D architectures perform better than 2D architectures. However, 3D architectures have limitations as they use more parameters and are computational complex [ 12 ]. Specifically, the dataset utilized for applying the 3D model is often reduced to half the size of the existing training data.…”
Section: Introductionmentioning
confidence: 99%